2010
DOI: 10.1007/s00442-010-1743-9
|View full text |Cite
|
Sign up to set email alerts
|

Does investment into “expensive” tissue compromise anti-parasitic defence? Testes size, brain size and parasite diversity in rodent hosts

Abstract: Species richness of parasite assemblages varies among host species. Earlier studies that searched for host-related determinants of parasite diversity mainly considered host traits that affect the probability of host encounter with parasites, whereas host traits related to defensibility against parasites have rarely been investigated. From the latter perspective, evolutionary investment in "expensive" tissue or organs (like testes or brain) may trade off against energetically costly anti-parasitic defences. If … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 100 publications
4
19
0
Order By: Relevance
“…A similar relationship between testes size and flea and helminth species richness has been found in other rodents which was possibly attributed to testosterone-mediated immunosuppression [40]. However, as our data show, the relationship between testosterone and parasites also depends on the parasite [16], [40], [41]. Similarly, a recent study in spiny lizards ( Sceloporus jarrovi ) demonstrated a positive association between plasma testosterone levels and mites but a negative association with endoparasites [16].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A similar relationship between testes size and flea and helminth species richness has been found in other rodents which was possibly attributed to testosterone-mediated immunosuppression [40]. However, as our data show, the relationship between testosterone and parasites also depends on the parasite [16], [40], [41]. Similarly, a recent study in spiny lizards ( Sceloporus jarrovi ) demonstrated a positive association between plasma testosterone levels and mites but a negative association with endoparasites [16].…”
Section: Discussionsupporting
confidence: 88%
“…This hypothesis was supported by our data which showed a negative association between testes size and immune function as well as a significant positive association between testes investment and number of lice, despite a low sample size. A similar relationship between testes size and flea and helminth species richness has been found in other rodents which was possibly attributed to testosterone-mediated immunosuppression [40]. However, as our data show, the relationship between testosterone and parasites also depends on the parasite [16], [40], [41].…”
Section: Discussionsupporting
confidence: 87%
“…In the wide taxonomic range presented by this study, host body mass does not seem a key factor shaping louse richness, as is also suggested by several earlier studies (Bordes et al 2011;Hughes and Page 2007;Krasnov et al 2004;Poulin 2007). We found, however, that body mass had a strong effect on the generic richness of Ricinids.…”
Section: Discussionsupporting
confidence: 68%
“…However, research on the interaction between host body size and parasite richness yielded contradictory results (see e.g. Poulin and Morand (2004), Poulin (2007) for reviews), suggesting that host body mass may not act as a general predictor of parasite diversity (Bordes et al 2011;Hughes and Page 2007;Krasnov et al 2004;). …”
Section: Introductionmentioning
confidence: 99%
“…Fourth, as the immunocompetence should be linked to parasite diversity (Ponlet et al 2011), trade-offs between levels of immunocompetence and expensive life history traits are expected (Bordes et al 2011;Morand 2015) as well as decreased immunocompetence with the loss of parasites and lower local biodiversity (Møller & Cassey 2004). A re-allocation of resources away from costly defences should be particularly pronounced at the wave-front of the invasion during the range expansion stage (White & Perkings 2012).…”
Section: Discussion: Research Neededmentioning
confidence: 99%